Innovative Solutions for Clean Transportation: Variable Compression Ratio Engine Performance using Algae Biodiesel - Arunraj R.; Selvam M.A.J.; Mohanty A.; Tahir A.M. (Malaysian Institute of Chemistry, 2025)
Boosting energy independence, improving air quality and the environment, and enhancing safety are all advantages of using biodiesel as fuel. This study focuses on evaluating the performance and emission properties of an algal biodiesel in a VCR engine.Third generation biofuel is used in a potential way to meet our future energy needs. Spirulina algae biodiesel, designated as B10, B20, B30, B40, and B100, is to be tested on a diesel engine by blending it with diesel on a volume basis. The spirulina algae blend athigher load levels lower fuel consumption from 2.8% to 13% compared to diesel. At greater loads, B100's brake thermal efficiency (BTE) drops to 4.8% and B20's BTE rises to 8.6% compared to the standard diesel. At about 9% lower, the biodiesel blend's EGT was lower than diesels. In full load conditions, algae blend considerably reduce harmfulemissions like CO, HC, NOx, and smoke when compared to diesel. ? 2024 Malaysian Institute of Chemistry. All rights reserved.